2016
DOI: 10.1007/s10661-016-5721-5
|View full text |Cite
|
Sign up to set email alerts
|

Climatic implications on variations of Qehan Lake in the arid regions of Inner Mongolia during the recent five decades

Abstract: The Qehan Lake Basin (QLB) and its system of lakes are located in a marginal monsoon zone and are extremely sensitive to global climate change. In this paper, using aerial photographs from different periods, in addition to MSS, TM, and ETM images, and combining these with regional topographic maps, we analyze lake area changes from 1958 to 2010 and the relation between Qehan Lake (QL) and climate variability. Our results indicate that there was a relatively high lake level in 1959, when the area and volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…These include corn, fruiting vegetables, grape, cotton, okra, stone fruit, and tobacco. By stimulating ryanodine receptors (ryanodine-sensitive calcium-release channels), flubendiamide disrupts the muscle functions in insects [ 5 ]. The wide use of this compound raised the concern about their impact on the environment, food safety and human health.…”
Section: Introductionmentioning
confidence: 99%
“…These include corn, fruiting vegetables, grape, cotton, okra, stone fruit, and tobacco. By stimulating ryanodine receptors (ryanodine-sensitive calcium-release channels), flubendiamide disrupts the muscle functions in insects [ 5 ]. The wide use of this compound raised the concern about their impact on the environment, food safety and human health.…”
Section: Introductionmentioning
confidence: 99%
“…The mean annual temperature is ∼ 3.5°C. The annual precipitation in the basin is ∼ 270 mm (Chun et al, 2017;Li et al, 2020), and more than 70% of the rainfalls occur in the rainy season (June to September) which is transported by the EASM from the Pacific and the Indian Ocean. The modern vegetation landscape in the region is typical dry steppes consisting primarily of grasslands, sandy deserts, and few forests.…”
Section: Geographical Settingmentioning
confidence: 99%
“…Liu and Ha (2015) has reconstructed the lake level since the past 6.8 ka by using paleolake shoreline records, and it showed that the paleolake level was at least 7 m higher than the present and gradually shrank till now. Chun et al (2017) and Chun et al (2018) has reported the variations of precipitation, temperature, and population in recent 50 years and further pointed out their effects on the changes of the lake level and vegetation coverage, and the results suggested that the variation of precipitation was the most fundamental factor for the recovery of vegetation and the rise of the lake level.…”
Section: Introductionmentioning
confidence: 99%
“…There are hundreds of lakes with areas of greater than 50 km 2 in northern China, and under the drastic climate change and unreasonable human development, a large number of these lakes have shrunk and become dry lake beds. These lake beds are generally flatter and have lower slopes (Chun et al, 2017), no vegetation cover, and a surface composed of loose salt-rich sedimentary particles (Yang L.-R. et al, 2007;Liu et al, 2010). These surfaces are exposed to windy conditions year-round and are highly susceptible to wind erosion, leading to unavoidable air pollution and environmental problems in arid and semi-arid regions (Shao et al, 2011;Von Holdt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%